PEGylated therapeutics in the clinic - Yongsheng Gao; Maithili Joshi; Zongmin Zhao; Samir Mitragotri (Wiley, 2024)
Abstract The covalent attachment of polyethylene glycol (PEG) to therapeutic agents, termed PEGylation, is a well‐established and clinically proven drug delivery approach to improve the pharmacokinetics and pharmacodynamics of drugs. Specifically, PEGylation can improve the parent drug's solubility, extend its circulation time, and reduce its immunogenicity, with minimal undesirable properties. PEGylation technology has been applied to various therapeutic modalities including small molecules, aptamers, peptides, and proteins, leading to over 30 PEGylated drugs currently used in the clinic and many investigational PEGylated agents under clinical trials. Here, we summarize the diverse types of PEGylation strategies, the key advantages of PEGylated therapeutics over their parent drugs, and the broad applications and impacts of PEGylation in clinical settings. A particular focus has been given to the size, topology, and functionalities of PEG molecules utilized in clinically used PEGylated drugs, as well as those under clinical trials. An additional section has been dedicated to analyzing some representative PEGylated drugs that were discontinued at different stages of clinical studies. Finally, we critically discuss the current challenges faced in the development and clinical translation of PEGylated agents.